Pakistan's accumulation of foreign exchange reserves during 2001 - 2006: benign or hostile!:excessive or moderate! intent or fluke! - Syed Kumail Abbas Rizvi; Bushra Naqvi; Muhammad Ramzan; Sayyid Salman Rizavi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
Excessive accumulation of foreign exchange reserves has emerged as an incredible monetary tool particularly after the East Asian crisis of 1997 which somehow seems able not only to stimulate economy but also to stabilize most vulnerable variables like exchange rate, debts and deficits. However there is a dire need to investigate the impacts of this strategy on the financial and economic performance of a country. We analyze the economy of Pakistan during the period of 2001-2006 with reference to the probable use of reserves accumulation as a monetary tool and find convincing evidences that reserves were being accumulated excessively in that period and impacted successfully in stimulating GDP's, Exports' and Imports' growth; stabilizing exchange rate; and reducing debt burdens and deficits. However, it is not evident that this strategy was designed and implemented intentionally by the monetary authorities following in the footsteps of other economies of the region. It rather seems to be a spontaneous policy or a fluke generated as an aftermath of 9/11 attacks that actually led to the strong capital inflows in the country by way of remittances and net foreign factor income.
Keywords: 330; Foreign exchange reserves; Excess reserves; Reserves accumulation; Exports led growth; Mercantilism; Währungsreserven; Exportinduziertes Wachstum; Pakistan